From the Navy to college transitioning from the service to higher education - Ventrone, Jillian; Blue, Robert W. (Rowman & Littlefield Publishers, 2015)
From the Navy to College is an education and career reference guide for sailors looking to join the Navy, already on active duty, or transitioning into the civilian sector. From getting started to degree completion, all available funding resources to help cover costs and Navy-based program options are detailed for the reader in order to assist throughout the course of an individual's chosen path.